Job demands and job resources and well-being of judges in South Africa - Elsie Rossouw (SA Journal of Industrial Psychology, 2020)
Orientation: Research has been conducted regarding job demands, job resources and well-being of individuals in a variety of jobs. However, no studies have focused on the work experiences of judges in an African context.